2012
DOI: 10.1590/s1516-35982012000100016
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of arginine with lysine in diets for laying Japanese quails

Abstract: To determine the relationship of arginine with lysine for Japanese quails during the period of production, an experiment was conducted using 360 subspecies of Japanese quails (Coturnix coturnix japonica) with 162 days of age, distributed in a completely randomized design. Diets were formulated with corn, soybean meal, sorghum and wheat bran containing 20.0% crude protein and 2,800 kcal ME/kg. The basal diet contained suboptimal level of lysine equal to 1% and was supplemented with five levels of L-arginine 99%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
18
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 10 publications
6
18
2
Order By: Relevance
“…AEW was 11.90 g, which is consistent with the results of Reis et al (2012), who found no significant effect of different digestible arginine concentrations on the AEW of birds.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…AEW was 11.90 g, which is consistent with the results of Reis et al (2012), who found no significant effect of different digestible arginine concentrations on the AEW of birds.…”
Section: Resultssupporting
confidence: 91%
“…The average ELR found in this study was 91.90%. The lack of an effect is consistent with the findings of Reis et al (2012), who evaluated arginine concentrations in egg-laying Japanese quails.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations